Problems of the Use of the Resources Internet in Professional Preparation of Master's Degree (Journal of Information Technologies in Education (ITE), 2008)
In article questions of improvement of preparation master's degree by means of resources of a network the Internet are staticized, the domestic and foreign resources the Internet focused on training master's degree are analysed; it is classified national Internet resources.